Profil berpikir statistis siswa SMP dalam menyelesaiakan masalah statistika deskriptif ditinjau dari tipe kepribadian - Naili, Imro’atin; Shodiqin, Ali; Sudargo, Sudargo (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study aims to determine the student’s statistical thinking profile off grade VIII A SMP N 1 Juwana students when solving descriptive statistical problems based on personality types. The descriptive qualitative method was used. The subjects taken were two students from grade VIII A SMP N 1 Juwana in the 2021/2022 scholastic year with details of one student of extrovert personalityy type and one studentt of introvert personality type. Data collected by personality type test, written test statistics, and interviews. Data validity is tested using triangulation techniques. According to the findings of this study, introverted subjects meet all indicators of statistical thinking, such as understanding and describing data in thee form of tables; organizing andd reducing data; representation of data; data analysis; and interpretation of data. While the subject extrovert doesn’t meet any of the five indicators of statistical thinking, namely the interpretation of the data.